Penerapan Model Kooperatif Teknik Kancing Gemerincing Untuk Meningkatkan Sikap Komunikatif Siswa Di Kelas Tinggi - Dita Ferbriani; Din Azwar Uswatun; Andi Nurochmah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
This research aims to improve the communicative attitude of students by using cooperative model of kancing gemerincing technique in social studies in high class. The type of this research is in the form of Classroom Action Research. Subjects in this study were 32 students of class V at Selabintana Wetan elementary school, consisting of 20 male and 12 female. Data collection techniques in this study were interviews, observations, questionnaires and field notes. The instruments used were interview guidelines, teacher activity observation sheets, student activity observation sheets, student communicative attitude observation sheets, student communicative attitude questionnaire sheets and field notes.The analysis technique used is quantitative descriptive. The results of the questionnaire study at pre-cycle obtained 40,36%, then the first cycle obtained 70,08% and in the second cycle obtained 86,78%. Thus it was concluded the cooperative model of kancing gemerincing technique can improve the communicative attitude of the V grade students of Selabintana Wetan elementary school in the academic year 2018/2019.